2016
DOI: 10.21649/akemu.v10i4.1267
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of FDPs and D-dimers in patients with breast cancer

Abstract: Seventy Five subjects were selected. Fifty subjects were breast cancer patients and 25 healthy control subjects were included. FDPs and D-dimers were performed by using commercially available kits. Results obtained were analyzed by using chi-square (X2) test and level of significance was done. A significant increase in the levels of FDPs and D-dimers were found in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…D-dimer is a product of cross-linked fibrin degradation by plasmin-induced fibrinolytic activity, and D-dimer levels are a biomarker of global hemostasis and fibrinolysis [21]. High D-dimer levels were associated with poor prognoses in patients with breast, [22,23] colon and rectum, [24,19] and lung [25,26] cancers. In the present study, it was demonstrated that elevated plasma levels of D dimer were associated with clinical cancer stages and metastasis in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is a product of cross-linked fibrin degradation by plasmin-induced fibrinolytic activity, and D-dimer levels are a biomarker of global hemostasis and fibrinolysis [21]. High D-dimer levels were associated with poor prognoses in patients with breast, [22,23] colon and rectum, [24,19] and lung [25,26] cancers. In the present study, it was demonstrated that elevated plasma levels of D dimer were associated with clinical cancer stages and metastasis in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%